Binding of Curcumin and its Long Chain Derivatives to the Activator Binding Domain of Novel Protein Kinase C - Majhi, Anjoy (2010)
Protein Kinase C (PKC) is a family of serine/threonine kinases that play a central role in cellular signal transduction. The second messenger diacylglycerol having two long carbon chains acts as the endogenous ligand for the PKCs. Polyphenol curcumin, the active constituent of Curcuma longa is an anticancer agent and modulates PKC activity. To develop curcumin derivatives as effective PKC activators, we synthesized several long chain derivatives of curcumin, characterized their absorption and fluorescence properties and studied their interaction with the activator-binding second cysteine-rich C1B subdomain of PKCδ, PKCε and PKCθ. Curcumin (1) and its C16 long chain analog (4) quenched the intrinsic fluorescence of PKCδC1B, PKCεC1B and PKCθC1B in a manner similar to that of PKC activator 12-O-tetradecanoylphorbol 13-acetate (TPA). The EC(50)s of the curcumin derivatives for fluorescence quenching varied in the range of 4-11 μM, whereas, EC(50)s for TPA varied in the range of 3-6 μM. Fluorescence emission maxima of 1 and 4 were blue shifted and the fluorescence anisotropy values were increased in the presence of the C1B domains similar to that shown by the fluorescent analog of TPA, sapintoxin–D, confirming that they were bound to the proteins. Molecular docking of 1 and 4 with novel PKC C1B revealed that both the molecules form hydrogen bonds with the protein residues. The present result shows that curcumin and its long chain derivatives bind to the C1B subdomain of novel PKCs and can be further modified structurally to improve its binding and activity.